The Common Man in the Focus of Modern European Values (Based on the Works of F. Backman) - E. A. Radaeva (Концепт: философия, религия, культура, 2024)
The relevance of this study is due to the fact that modern democratic values, entrenched in Western countries, including at the legislative level, are widely discussed in Russian society today: how much the freedoms and restrictions introduced in the 21st century correspond to the needs of the average citizen, that is, in this case, the average European. The material for studying this issue was the works of the world-famous Swedish writer Frederik Backman — the novels A Man Called Ove (2012) and Things My Son Needs to Know About the World (2012), as well as the film adaptations of the first novel (Swedish in 2015 and American in 2022). The aim of the study is to determine the ideological attitudes conveyed by the artistic worlds of the works under study. To achieve this goal, the theoretical and methodological frameworks were analyzed, opening up the possibility of studying values through the prism of cultural research of fiction and cinematography. Other tasks included: identifying the key features of the literary and film versions of the novel A Man Called Ove, to establish the specifics of their value framework, and describing the key moments of the novel Things My Son Needs to Know About the World so as to determine the values conveyed by this work. Based on the axiological and anthropological prisms within the framework of the cultural studies approach, intertextual, intermedial and narrative analysis of the texts of each of the books and the two film adaptations of A Man Called Ove is applied. The biographical method and the method of reconstructing the views of the hero of the work of art were also used. As a result of the undertaken reconstruction, a cultural model of analysis of European values of the common man was created thanks to their reflection in literature and cinema. The possibilities and limits of using the cultural method in the analysis of complex and multi-level artistic material were determined. The contradictions that permeate various versions of the film adaptation of the novel A Man Called Ove were highlighted and the characteristic discrepancies between the two novels by F. Backman are described. If the first describes the path of gaining tolerance for everything new by a person of the old school, then the second develops the theme of the absurdity of the modern world, its lack of rootedness in traditions, and discusses the helplessness and defenselessness of man in new realities, such as when, alongside the maximum of democratic freedoms, there arises a paradoxical maximum of unfreedom for the individual. It is also indicative in the axiological context that the directors were only interested in the first book, which was more convenient not only in terms of the script, but also in terms of the ideology, as a locomotive of loyalty to representatives of minorities, and therefore offering more chances to receive international awards.